Advances in oral health knowledge of Greek navy recruits and their socioeconomic determinants - Silvestros Spyros; Souliotis Kyriakos; Vrahopoulos Theofilos P; Zavras Athanasios I; Vrotsos Ioannis (BMC, 2002)
Abstract Background The aim of the present study was to evaluate temporal changes on oral health knowledge and attitudes among two populations of young Greek males (age 19-29 years) undergoing their military training. A secondary aim was to identify socioeconomic trends that may have influenced the above. Methods A total of 2,764 healthy subjects (1511 in 1985, and 1253 in 1996) answered a standardized questionnaire of oral health issues. Respondents were stratified in 3 groups, according to their educational status (ES); their responses were compared using the chi-square statistic. The evaluation of socioeconomic indicators utilized longitudinal data from the national Household Expenditures Survey. Results An overall improvement was noted in the majority of "Knowledge" and "Attitudes" variables in 1996, as compared to 1985. Education seems to play an important role in both knowledge and attitudes. These changes may also be partially attributed to a shift in consuming standards from the coverage of main needs to income disposal directed towards the achievement of better quality of life.